2021
DOI: 10.1177/10422587211024510
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Incubator and Accelerator Participation on Nanotechnology Venture Success

Abstract: This study investigates how venture development programs such as private incubators, university incubators, and accelerators influence the success of participating nanotechnology startups. With the recent growth in such programs, empirical work is needed to compare their impact on participants across programs and with nonparticipants. Using data on firm bankruptcies, liquidation, government grants, and venture capital, we find benefits, but the influence of each venture development program varies greatly. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 111 publications
2
23
0
1
Order By: Relevance
“…The relationship we identify between a company's age and its decreasing dependence on its entrepreneurial ecosystem is consistent with the results of Sorenson and Stuart (2001) and Presutti et al (2013) but contradicts those of Harrison et al (2010). These results concur with those suggesting that strong local integration is a first step for young start-ups to establish their legitimacy and competitiveness (Lechner and Leyronas, 2012;Scheidgen, 2021;Woolley and MacGregor, 2021).…”
Section: Start-ups In Entrepreneurial Ecosystemssupporting
confidence: 78%
See 1 more Smart Citation
“…The relationship we identify between a company's age and its decreasing dependence on its entrepreneurial ecosystem is consistent with the results of Sorenson and Stuart (2001) and Presutti et al (2013) but contradicts those of Harrison et al (2010). These results concur with those suggesting that strong local integration is a first step for young start-ups to establish their legitimacy and competitiveness (Lechner and Leyronas, 2012;Scheidgen, 2021;Woolley and MacGregor, 2021).…”
Section: Start-ups In Entrepreneurial Ecosystemssupporting
confidence: 78%
“…We believe that this apparently paradoxical result of the lower importance of local actors for smaller innovative start-ups could reflect additional conditions: First, the choice of highly specialized niche strategies that reduce the likelihood of finding specific local partners and would encourage companies to maintain relationships with more distant actors; and second, a lack of local anchoring and limited relational capacity of smaller firms that reduce their ability to interact with specific partners locally compared to larger more legitimate actors (Lechner and Leyronas, 2012;Woolley and MacGregor, 2021).…”
Section: Start-ups In Entrepreneurial Ecosystemsmentioning
confidence: 99%
“…Therefore, understanding the micro foundations of EE and the interdependencies between their actors has recently been identified as a promising research avenue (Audretsch et al, 2021;Kansheba and Wald, 2020;Wurth et al, 2022). To answer this call, we shed light on such interdependencies by investigating how actors gain legitimacy in EE to become perceived as fully legitimate, and thus undisputed, members and contributors of their EE (Kuratko et al, 2017;Thomas and Autio, 2014;Woolley and MacGregor, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence shows that multiple intermediaries may target the same actors over time (Woolley & MacGregor, 2021;Kobarg et al, 2019). Hochberg and Fehder (2015) observed that intermediaries' interventions in a particular region play a catalyzing role in the establishment of other interventions to further encourage entrepreneurial activities.…”
Section: The Effects Of Collaboration Depth and Breadth On Capability...mentioning
confidence: 99%
“…These collaborations between intermediaries and small enterprises can be characterized in terms of breadth and depth (Kobarg et al, 2019;Leiponen & Helfat, 2010). Collaboration depth relates to the number of years of collaboration, standing for the intensity of the relationship with intermediaries; collaboration breadth refers to the diversity of sources of collaboration-as firms normally establish relationships with more than one intermediary (Woolley & MacGregor, 2021;Goswami, Mitchell, & Bhagavatula, 2018). Determining how firms and intermediaries collaborate is important for firms' survival and performance, because each type of collaboration may lead to different types of capabilities (Kobarg et al, 2019;Love, Roper, & Vahter, 2014;Srinivasan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%